2019
DOI: 10.1038/s41598-019-43766-7
|View full text |Cite
|
Sign up to set email alerts
|

Cathelicidins and the Onset of Labour

Abstract: Preterm birth, defined as delivery before 37 weeks of gestation, is the leading cause of neonatal mortality and morbidity. Infection and inflammation are frequent antecedents of spontaneous preterm birth. Cathelicidin, an antimicrobial host defence peptide, is induced by infection and inflammation and although expressed in the reproductive tract and fetal tissues, its role in the pathogenesis of spontaneous preterm birth is unknown. Here we demonstrate that cathelicidin expression is increased at RNA and prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Given that cervical ripening is associated with neutrophil influx and inflammation mediated by chemokines and cytokines 18 , and that we previously demonstrated strong association between CVF cathelicidin and cytokine concentration with cervical shortening 12 , the rise in CVF cathelicidin (and HNE) concentration prior to cervical shortening (median 18 +3 weeks) was not unexpected. Cathelicidin has been shown to mediate the pro-inflammatory response in mouse models of term and sPTB with cathelicidin-deficient mice less susceptible to lipopolysaccharide induced sPTB 19 . Cathelicidin may have a responsive role to tissue damage around the time of cervical shortening, stimulating angiogenesis 20 , re-epithelialisation 21 , and promoting wound healing and immune cell infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…Given that cervical ripening is associated with neutrophil influx and inflammation mediated by chemokines and cytokines 18 , and that we previously demonstrated strong association between CVF cathelicidin and cytokine concentration with cervical shortening 12 , the rise in CVF cathelicidin (and HNE) concentration prior to cervical shortening (median 18 +3 weeks) was not unexpected. Cathelicidin has been shown to mediate the pro-inflammatory response in mouse models of term and sPTB with cathelicidin-deficient mice less susceptible to lipopolysaccharide induced sPTB 19 . Cathelicidin may have a responsive role to tissue damage around the time of cervical shortening, stimulating angiogenesis 20 , re-epithelialisation 21 , and promoting wound healing and immune cell infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…Here, the authors demonstrated that neutrophil cathelicidin is important in controlling T‐cell responses by inducing Th17 cells, suppressing Th1 differentiation and inhibiting the death of IL‐17‐producing cells. Cathelicidin also plays a role in mediating pro‐inflammatory responses during labour [ 79 ]. In addition to cathelicidin, many other mediators such as MPO, elastase, lactoferrin, ARG‐1 and gelatinase are released from granules during neutrophil degranulation and have been demonstrated to affect the development of T‐cell responses [ 80 ].…”
Section: The Cross‐talk Between Neutrophils and T Cellsmentioning
confidence: 99%
“…Although blood neutrophils have a short life-span, neutrophils in the decidua have greatly increased survival, mediated in part by up-regulating anti-apoptotic mediators including Bcl-2 family members (e.g., Bcl2A1, called Bfl-1 in humans) (84,152). Neutrophils can amplify the inflammatory response and neutralize microorganisms by releasing neutrophil extracellular traps (NETs), producing antimicrobial enzymes such as defensins, neutrophil elastase, and myeloperoxidase (MPO), and releasing reactive oxygen species (ROS) (153)(154)(155). Neutrophilderived pro-inflammatory mediators can trigger preterm labor and matrix metalloproteinases (MMPs) can weaken the collagen scaffolding, resulting in preterm rupture of membranes (156)(157)(158).…”
Section: Neutrophilsmentioning
confidence: 99%